Artemether Ameliorates Non-Alcoholic Steatohepatitis by Repressing Lipogenesis, Inflammation, and Fibrosis in Mice - Xu, Jia; He, Xiaoyun; Huang, Xianghui; Zhang, Feng; Ren, Xinxin; Asakiya, Charles; Li, Yue; Huang, Kunlun (Frontiers in Pharmacology, 2022)
Background: Non-alcoholic fatty liver disease (NAFLD) is a widespread disease, but no recognized treatment drug exists. Previous studies have shown that Artemether (Art) can ameliorate carbon tetrachloride (CCl4)-induced liver fibrosis in mice. This study set out to observe the therapeutic impact of Art on non-alcoholic steatohepatitis (NASH). Methods: Model mice were provided with a methionine and choline deficiency diet (MCD) for 4 weeks or a high-fat diet (HFD) for 28 weeks, respectively, and then treated with Art. RNA sequencing (RNA-Seq) analyzed the gene expression change of Art treatment. The molecular mechanism of the therapeutic effects of Art on NASH was studied in mouse liver and HepG2 cells. Results: Art treatment significantly attenuated MCD diet or HFD diet-induced NASH mice of hepatic lipid accumulation and liver damage. The RNA-Seq analysis revealed lipid metabolism as a major pathway suppressed by Art administration, in addition to the regulation of inflammation pathways. Mechanistically, Art reduced lipid accumulation by repressing de novo lipogenesis on sterol regulatory element-binding protein-1c (SREBP-1c), acetyl-CoA carboxylase (ACC), fatty acid synthase (FASN), stearoyl-CoA desaturase (SCD1), promoting lipolysis on peroxisome proliferator-activated receptor-γ co-activator-1α (PGC1α), adipose triglyceride lipase (ATGL), carnitine palmitoyltransferase I (CPT1a) in NASH mice liver and HepG2 cells. In addition, Art inhibited the secretion of pro-inflammatory factors and reduced the inflammatory infiltration by effectively inhibiting M1 macrophage activation. Furthermore, Art inhibited transforming growth factor-beta1 (TGF-β)/SMAD signaling pathway mediates the development of liver fibrosis. Inclusion: Art improved fat deposition by repressing de novo lipogenesis and promoting lipolysis in vivo and in vitro. Furthermore, Art improved inflammation and fibrosis with a significant effect. It is a prospective therapeutic agent for NASH.